The Graduate’s Portrait of Competence and Technology’s Mastery in Biology Learning - Hutasoit, Leonard R.; Kismiati, Dyah Aniza; Setyawan, Danang Budi; Wahyuningsih, Tri; Nurdin, Gusti (Jurnal Pijar Mipa, 2024)
This survey research was conducted with the aim of knowing how the portrait of mastery of competence of Open University Biology Education study program graduates as biology teachers also their mastery of technology in learning. The graduates are junior high school teachers and high school teachers. The research sample was taken randomly until a sample of 94 graduates and 47 graduate users were obtained in various regions in Indonesia, such as Bogor, Central Jakarta, Pontianak, Serang, Cianjur, Pekanbaru and Bandung. The instruments used are questionnaire instruments with Likert scales and interview guidelines conducted to graduate users and graduates. Furthermore, the data is analyzed descriptively to get a portrait of mastery of competence and technology in learning. The results of the data analysis showed that the portrait of mastery of competence was categorized as very good / high, which was indicated by a value of 98.94% (graduate self-reflection) and 97.87% (assessment by graduate users). In addition, from the results of the analysis, it is also known that the portrait of mastery of technology in graduate learning is categorized as very good / high with a value of 91.49% (based on graduate self-reflection and assessment by graduate users)